Islamic Boarding Schools Facing Global Competition: An Overview of Strategic Plans at PP DDI Wal Ersyad Konawe Selatan (Pesantren Menghadapi Persaingan Global: Tinjauan Rencana Strategis di PP DDI Wal Irsyad Konawe Selatan) (Shautut Tarbiyah, 2023)
This article aims to analyze: 1) Directions for the development of the DDI Wal Ersyad Lamooso Islamic Boarding School; 2) Strategy to face the era of global competition at the DDI Wal Ersyad Lamooso Islamic Boarding School; 3) The role of leadership in strategic planning at the DDI Wal Irsyad Lamooso Islamic Boarding School. The research was conducted qualitatively with a narrative approach. The results of the study show that: It cannot be said that the Pondok has the ability to make new breakthroughs, socialize the institution, create branding that is able to attract people's interest. This is due to the ability of Islamic boarding schools in a system of collaboration and collaboration between institutions, both local government and private institutions. Next, Islamic boarding schools have not been able to formulate in detail long-term planning as a basis for running the program. This research suggests: 1) Islamic boarding schools can prepare themselves both in conceptual form and real programs in facing the globalization era; 2) Creating lines of cooperation both domestically and abroad; 3) Leaders must be able to embrace all elements to formulate planning for Islamic boarding schools, priority programs that are long, medium or short term.Keywords:     Islamic Boarding School Leadership, Global Competition